Poster 104: The Role of Patient Demographic Factors in the Composition of Bone Marrow Aspirate Concentrate: A Flow Cytometry Analysis. Issue 7 (30th July 2022) - Tauro, Tracy; Credille, Kevin; Dandu, Navya; Wong, Stephanie; Chahla, Jorge; Forsythe, Brian; Yanke, Adam; Cole, Brian; Verma, Nikhil; Huddleston, Hailey
Objectives: Bone marrow aspirate concentrate (BMAC) is one type of orthobiologic that has gained increased popularity over the last decade for a variety of orthopedic procedures. Multiple factors have been demonstrated to influence the MSCs concentration and chondrogenic potential in BMA and thus BMAC, ranging from aspiration location to amount extracted to peripheral blood platelet count. Some studies have suggested that age may affect chondrogenic potential of BMAC derived MSCs but may not affect initial MSC concentration. Therefore, the purpose of this study was to 1) investigate the concentration value and variance BMAC content and 2) investigate the effects of donor age, sex, and other demographic factors on the amount of MSCs as measured by flow cytometry in bone marrow aspirate concentrate (BMAC). Methods: A review of patients who underwent BMAC treatment as part of a clinical trial were enrolled and complete BMAC flow cytometry data were included in analysis. Chart review was performed to identify patient demographic factors to determine their relationship to flow cytometry cell count. Flow cytometry was performed on both patient bone marrow aspirate (BMA) and BMAC samples to identify multipotent MSC phenotype defined as cell-surface co-expression of the antigens CD105, CD73, and CD90 (≥95% positive) and the absence of hematopoietic lineage markers CD45, CD34, CD14 or CD11b, CD79a or CD19, and HLA-DR (≤2% positive). The ratio of cells in BMA: BMAC samples was calculated, and Spearman correlations and Kruskall-Wallis tests were used to determine the relationship of cell concentration to demographic factors. Results: A total of 80 patients were included in analysis (49% male, mean age: 49.93±12.17 years). Mean concentration of BMA and BMAC was 2, 048.13±2, 004.14 MSCs/mL and 5618.87±7568.54 MSC/mL, respectively, with a mean BMAC:BMA ratio of 4.35 ± 2.09 (Figure 1 ). A significantly higher MSC concentration was observed in the BMAC samples (P=0.005). No patient demographic factors (age, sex, height, weight, BMI, smoking status) significantly impacted MSC concentration in the BMAC samples. Conclusions: This study validates that BMAC concentrates and increases MSCs from BMA approximately four-fold. In addition, in opposition to our hypothesis, no demographic factors affected the final number of MSCs observed with flow cytometry analysis. These preliminary results suggest that BMAC successfully concentrates BMA and provides a higher number of MSCs. Baseline patient characteristics likely have minimal effects on the number and concentration of MSCs in BMAC, and therefore may not limit patient selection for BMAC for clinical use. Figure 1. Distribution of the ratio of BMAC to BMA